Indicator - based management recommendations for an artisanal bottom - longline fishery in Costa Rica, Central America - Bystrom, Andrew B. (2017)
There is a growing need to strengthen the small-scale fishing sector with emerging governance methods that improve fishers’ threatened livelihoods. Therefore, this study’s aim was to develop management recommendations, based on easily interpreted conclusions that can be used to address the socio-ecological difficulties that the artisanal, bottom-longline fishery in Bejuco, Pacific coast of Costa Rica faces. The results of previously recorded fisher socio-ecological perceptions and an evaluation of the spotted rose snapper’s, Lutjanus guttatus, population dynamics were assigned a measurable set of indicators in reference to the fishery’s natural, human and management sub-systems. This was done via the traffic light method with easily interpreted colors based on a review of similar published fisheries studies. According to these results, a stock assessment for the fishery’s target species and research to determine the composition and magnitude of the fishery’s discarded species were recommended. Fisher economic dependence on bottom-longline activities led to the recommendation to develop alternative livelihood strategies. Also, the promotion of alternative markets and sustainability certification strategies for the snapper fishery are advised. Enlargement of the multi-use marine protected areas within the fishery’s grounds and improvement of their management strategies is also recommended. In order for this to occur, improved resource user coordination in the form of a fisher association that has the capability to lobby for increased enforcement of the protected areas from destructive fisheries must be realized. Doing so would aid the development of a local management plan and participatory governance system. Such an initiative would justify the development of community lead marine protected area management regimes.